2020
DOI: 10.5552/drvind.2020.1949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Resin from Wild Pistachio Trees on Physical Properties and Durability of Beech Wood

Abstract: This study was carried out to investigate the physical properties and decay resistance of beech wood treated with natural pistachio resin (PR) from Iranian wild pistachio trees (Pistacia atlantica), alone and in combination with boric acid (BA). Wood samples were impregnated with different concentration of PR dissolved in ethanol (3 to 20 %) with vacuum-pressure technology. The combination of PR (20 %) and BA (2 %) was also conducted to evaluate any interaction or synergistic effects. The water absorption, vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Since the mass loss is relatively less for treated blocks, it can be inferred that the extract might have formed a protective layer over the surface of wood blocks, at least throughout fungal decay (12 weeks). These results were similar to those previously reported by Nayeri et al (2017), Kwaśniewska-Sip et al (2018), Ouyang et al (2018), Izadyar et al (2020), Ahadnezhad et al (2021). The differences in ML varied depending on the plant extracts and the concentration used.…”
Section: Decay Testsupporting
confidence: 92%
“…Since the mass loss is relatively less for treated blocks, it can be inferred that the extract might have formed a protective layer over the surface of wood blocks, at least throughout fungal decay (12 weeks). These results were similar to those previously reported by Nayeri et al (2017), Kwaśniewska-Sip et al (2018), Ouyang et al (2018), Izadyar et al (2020), Ahadnezhad et al (2021). The differences in ML varied depending on the plant extracts and the concentration used.…”
Section: Decay Testsupporting
confidence: 92%
“…GC–MS analysis of the essential oils extracted using hydrodistillation of the different parts of PA resulted in the identification of chemical constituents with high antioxidant activities (Ahmed et al, 2021; Bozorgi et al, 2013; Mahjoub et al, 2018; Mohammadi et al, 2019). Different studies revealed that PA oleoresin essential oil contained high amounts of monoterpenes such as α‐pinene and β‐pinene, with a wide range of 55.0%–97.2% and 3%–16%, respectively (Elyasi Ghahfarrokhi et al, 2022; Izadyar et al, 2020; Savedoroudi et al, 2016). In addition, the findings of previous studies demonstrate that PA is a promising source of phenolic and flavonoid compounds.…”
Section: Discussionmentioning
confidence: 99%